Characteristics and outcomes of fetal ventricular aneurysm and diverticulum: combining the use of a new technique, fetal HQ - Zhao, Liqing; Wu, Pengfei; Jiao, Xianting; Zhang, Minjie; Jing, Wenhao; Wu, Yurong; Chen, Sun (Frontiers in Pediatrics, 2023)
Objectives: Congenital ventricular aneurysms or diverticulums (VA/VD) are rare cardiac anomalies and lack prenatal evaluation data. The present study was to provide the prenatal characteristics and outcomes from a tertiary center and use new techniques to evaluate the shape and contractility of these fetuses. Methods: Ten fetuses were diagnosed with VA or VD, and 30 control fetuses were enrolled. Fetal echocardiography was performed to make the diagnosis. The prenatal echo characteristics and follow-up data were carefully reviewed. The shape and contractility measurements of the four-chamber view and both ventricles were measured and computed using fetal HQ. Results: A total of ten fetuses were enrolled, including 4 cases of LVD, 5cases of LVA, and one case of RVA. Four cases chose to terminate the pregnancy. The RVA was associated with a peri-membranous ventricular septal defect. Two cases had fetal arrhythmia, and one case had pericardial effusion. After birth, one case underwent surgical resection at five years old. The 4CV GSI of free-wall located VOs was significantly lower than the apical ones and the control group( p＜0.01). 4/5 apical left VOs had significant higher (＞95th centile) SI in base segments. 3/4 left VOs in free-wall had significant lower (＜ 5th centile) SI in majority of 24 segments. Compared to the control group, the LV GS, EF, and FAC were significantly decreased (p＜0.01), while the LV CO of cases was in normal ranges. The transverse FS of affected segments of ventricles was significantly lower than the other ventricle segments (p＜0.01). Conclusions: Fetal HQ is a promising technique to evaluate the shape and contractility of congenital ventricular aneurysms and diverticulums.